2016
DOI: 10.1111/hdi.12499
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of assisted procedures for arteriovenous fistula maturation without compromising access patency

Abstract: Our results support that idea that assisted maturation procedures can ensure the success of immature AVF without compromising long-term patency. These procedures can be considered more positively for increasing AVF use for VA placement in HD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 20 publications
1
8
1
Order By: Relevance
“…Age has been described as an important factor influencing the AVF patency in several studies, [ 5 , 17 , 21 ] but, no significance was observed in our study. On the contrary, patients more than 65 years of age showed longer secondary patency, but this is not concluded with statistical significance in our study.…”
Section: Discussioncontrasting
confidence: 94%
See 2 more Smart Citations
“…Age has been described as an important factor influencing the AVF patency in several studies, [ 5 , 17 , 21 ] but, no significance was observed in our study. On the contrary, patients more than 65 years of age showed longer secondary patency, but this is not concluded with statistical significance in our study.…”
Section: Discussioncontrasting
confidence: 94%
“…To solve this problem, several reports suggest mapping, vascular access counseling as well as surgical ligation or embolization of accessory vein and PTA. [ 3 , 5 , 8 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the entire study period, the initial VAIVT success rate was 93.8%, similar to that reported by previous studies [19][20][21][22][23][24][25]. In addition, the 1-year patency rate was 39.7% (Fig.…”
Section: Initial Success and Primary Patency Ratessupporting
confidence: 87%
“…Problems related to HD VA affect the survival rate of ESRD patients. Various techniques of endovascular therapy resulted in a breakthrough development in the treatment of HD VA [1113]. However, the lesion of CV is much less responsive to endovascular therapy than that of a peripheral location.…”
Section: Treatmentmentioning
confidence: 99%